ID 383 – On the impact of stimulus intensity on vestibular evoked potentials (VestEPs). Issue 3 (March 2016) - Ertl, M.; Moser, M.; Boegle, R.; Conrad, J.; Dieterich, M.
Abstract : Objective: Recently published studies describe neural correlates of vestibular stimulation by means of evoked potentials. While some groups use loud click sounds or taps to the forehead we use passive body movements to study vestibular evoked potentials (VestEPs). Here, we investigated the impact of the acceleration intensity on the latency and amplitudes of the previously discovered VestEPs. Methods: The EEG of eleven healthy subjects was recorded while they were seated in a racing chair mounted on a motion platform (hexapod). During the experiment the platform performed 216 translational movements using three different acceleration intensities. The EEG was analyzed in order to study the evoked potentials and the scalp topographies. Results: We could replicate the characteristic potentials of vestibular stimulation as observed by our group in previous experiments. Additionally, we could show that the amplitudes of the VstEPs increased with higher accelerations. Conclusions: Our data revealed that as in other sensory systems, e.g., the auditory, the stimulus intensity modulates the VestEPs amplitudes. Acknowledgements: The work was supported by Deutsche Stiftung Neurologie, Graduate School for Systemic Neuroscience (GSN) and theGerman Federal Ministry of Education and Research (BMBF Grant code01EO1401 ).